2021
DOI: 10.1080/19490976.2021.1912562
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the neonatal microbiome: will the pandemic cost infants their microbes?

Abstract: Mortality and morbidity from infections in children remains low, including an exceedingly low rate of horizontal and vertical transmission. However, unforeseen complications to childhood health have emerged secondary to the pandemic. Few studies to date have examined unintended complications of the pandemic in newborns and infants. In this Commentary, we discuss the impact that COVID-19 may have on inheritance of the newborn microbiome and its assembly throughout the first years of life. In the early stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Even if transmission of COVID-19 through breastfeeding appears unlikely, the infection could affect HMM, with breast milk being an expression of connection between mother and child [ 35 ]. During pregnancy, intestinal dysbiosis associated with COVID-19 inflammation could affect the composition of a newborn’s pioneer bacterial communities [ 8 ]. It was observed that greater the severity of the disease, greater was the intestinal dysbiosis.…”
Section: Human Milk Microbiota Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if transmission of COVID-19 through breastfeeding appears unlikely, the infection could affect HMM, with breast milk being an expression of connection between mother and child [ 35 ]. During pregnancy, intestinal dysbiosis associated with COVID-19 inflammation could affect the composition of a newborn’s pioneer bacterial communities [ 8 ]. It was observed that greater the severity of the disease, greater was the intestinal dysbiosis.…”
Section: Human Milk Microbiota Compositionmentioning
confidence: 99%
“…We can hypothesize that the above findings might be partially applicable to COVID-19 affected pregnant women, and since it is supposed that composition of the breast milk impacts the infant’s intestine, further studies on the changes in the microbiota of pregnant women affected by COVID-19 are necessary [ 35 ]. What is certain is that the pandemic has influenced HMM composition in several phases, both directly and indirectly, which can be substantiated by the fact that the placentas of women affected by severe acute respiratory syndrome have increased rates of vascular malperfusion features that can alter normal bacterial exchange between the mother and child [ 8 ]. Moreover, the presence of respiratory infection, enhances the probability of a C-section delivery, with a consequential reduction in maternal transfer of vaginal microbes to newborns [ 8 ].…”
Section: Human Milk Microbiota Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, on the other hand, are focusing on the impact that maternal factors, antibiotic use, host genetics, ethnicity, and even COVID-19 infection can have on microbiota development [ 102 , 103 , 104 ]. Therefore, alterations of the intestinal ecosystem, known as dysbiosis, during this critical period of development are often associated with various kinds of pathologies.…”
Section: Development Of the Gut Microbiomementioning
confidence: 99%
“…Identifying the potential routes of mother-to-child-transmission of COVID-19 is of particular importance for healthcare professionals to be able to provide appropriate care and advice for pregnant and breastfeeding women to minimize the risks posed to their infant. Additionally, understanding the impact of maternal COVID-19 infection on the development of the neonatal microbiome will also be important in providing appropriate nutritional support for these children during infancy [49]. It is well known that some viral infections during pregnancy can have devastating effects on the developing fetus, yet there have been few large-scale studies which involve the collection of samples from pregnant women infected with COVID-19 to determine the routes through which the virus, and immunity to the virus, can be passed from mother to child.…”
Section: Plos Onementioning
confidence: 99%